Poems of Lamentation of Terez - Hassan, Jehat; Hassan, Kovan (Humanities Journal of University of Zakho, 2023)
In the past, grief and lamentation for the dead were one of the main purposes of poetry. However, with the passage of time, this purpose witnessed great changes as the Kurdish literature witnessed such developments. This means that grief and lamentation moved from the level of grief of relatives and clan to greater goals. The death of leaders, artists, writers, and fighters also became a tool for grief and lamentation in most of the stages of the Kurdish literature, especially in poems. Grief and lamentation for the dead were among the important topics and became the focus of poets’ interest, especially in the traditional and modern poems. Many of the Kurdish poets cared about lamentation in the modern era, as they wrote poems of sadness and lamentation for different personalities and events. Terez is among those poets who paid great attention to lamentation, as it is possible to clearly show the direction of this change in his poems, and we tried to know the extent and quality of Terez’s interest in the subject of grief and lamentation. Was he able to express it well and meet the required level? To what extent did he care about this topic? For this reason, we have tried in this research entitle (Poems of Lamentation of Terez) to show the innovations and changes that Terez made in this aspect. This research study adopted both the (descriptive and analytical) approaches.